PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, IDENTIFIKASI ORGANISASI, KEPRIBADIAN PROAKTIF DAN OCB TERHADAP WORK ENGAGEMENT (Studi Pada Guru Dan Tenaga Kependidikan Di SMK Negeri 67 Jakarta) - Natalina Mutiara Purnomo; Ahmad Setiawan Nuraya (Ibs Press, 2023)
The purpose of this research is to learn about Transformational Leadership, Organizational Identification, Proactive Personality and OCB to Work Engagement. The object of this research is SMK Negeri 67 Jakarta. The population in this study were all teachers and education personnel at SMK Negeri 67 Jakarta, totaling 28 respondents. The method used in this research is quantitative with primary data collection through questionnaires. Data were analyzed using Partial Least Square-Structural Equation Modeling (PLS-SEM) with SmartPLS 3 Application. The results showed that: 1) Transformational Leadership had a positive and insignificant effect on Work Engagement. 2) Organizational identification has a positive and significant effect on Work Engagement. 3) Proactive Personality has a positive and significant effect on Work Engagement. 4) Organizational Citizenship Behavior (OCB) has a positive and insignificant effect on Work Engagement.